Insights into Advanced Retinopathy of Prematurity Using Handheld Spectral Domain Optical Coherence Tomography Imaging - Chavala, Sai H. (2009)
PURPOSE: To elucidate the subclinical anatomy of retinopathy of prematurity (ROP) using spectral domain optical coherence tomography (SD OCT). DESIGN: Prospective, observational case series. PARTICIPANTS: Three low-birth-weight, severely premature infants. METHODS: Clinical examination was performed using a portable slit lamp and indirect ophthalmoscope. Imaging was performed by using a handheld SD OCT device and Retcam (Clarity Medical Systems, Pleasanton, CA) or video-indirect recording. Spectral domain optical coherence tomography imaging was conducted without sedation at the bedside in the neonatal intensive care unit on 1 patient. The other 2 patients had an examination under anesthesia with SD OCT imaging in the operating room. MAIN OUTCOME MEASURES: In vivo determination of vitreoretinal morphology, anatomy, and pathology by clinical examination, imaging, and SD OCT. RESULTS: Linear and volumetric imaging was achieved with the handheld system in infant eyes despite tunica vasculosa lentis and vitreous bands. Imaging was not possible in eyes with notable vitreous hemorrhage. Analysis of SD OCT images revealed preretinal structures (ranging from 409 to 2700 μm in width and 212 to 440 μm in height), retinoschisis, and retinal detachment in the posterior pole of patients with advanced ROP. Both the retinoschisis and the preretinal structures were not identified on conventional examination or imaging by expert pediatric ophthalmologists. The preretinal structures varied in location and size, and may represent preretinal fibrovascular proliferation. Some were found in close proximity to blood vessels, whereas others were near the optic nerve. CONCLUSIONS: Handheld SD OCT imaging can be performed on the sedated or nonsedated neonate and provides valuable subclinical anatomic information. This novel imaging modality can reveal the location and extent of posterior ROP pathology not evident on standard examination. This could affect future clinical decision-making if studies validate a management strategy based on findings from this imaging technique.